Impact of Recurrent Parasitic Infections on Growth and Development in Children Under Five Years - Muhammad Aamir Aziz, Sumaira Shouket, Umar Farooq, Mahrukh Bashir, Wajid Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Parasitic infections remain a major cause of morbidity among children in low- and middle-income countries. Objective: This study aimed to evaluate the impact of recurrent parasitic infections on growth and developmental outcomes in children under five years of age. Methodology: This cross-sectional analytical study was conducted at Sahiwal Teaching Hospital, Sahiwal from January 2022 to June 2022. A total of 205 children aged 6–59 months were enrolled using non-probability consecutive sampling. Participants were categorized into three groups: no infection (n=70), single infection (n=68), and recurrent infections (≥2 episodes within the past year, n=67). Data on sociodemographic factors, feeding practices, and sanitation were collected using a structured proforma. Results: Children with recurrent parasitic infections showed significantly lower mean height-for-age (−2.15 ± 1.19) and weight-for-age (−1.92 ± 1.15) z-scores compared to those without infection (p < 0.001). The prevalence of stunting and underweight status was 40.3% and 44.8%, respectively, among the recurrent group. Anemia was observed in 72% of recurrently infected children versus 38% of infection-free peers (p < 0.001). Developmental delays were notably higher in the recurrent group especially in language (37.3%) and gross motor domains (31.3%). A moderate negative correlation was found between infection frequency and both height-for-age (r = −0.46) and weight-for-age (r = −0.39), while a positive correlation existed with developmental delay scores (r = +0.42). Conclusion: It is concluded that recurrent parasitic infections significantly impair physical growth and developmental milestones in children under five years of age. Poor sanitation, unsafe water, and inadequate hygiene practices were identified as major contributing factors. Keywords: Parasitic infection, recurrent infection, child development, stunting, anemia, growth retardation